Sharing hydropower revenues in Nepal, over time and across districts and regions - Balasubramanya, Soumya; Giordano, Mark; Wichelns, Dennis; Sherpa, T. (Elsevier, 2014)
In recent years, the Government of Nepal has increased the amount of revenue it collects from hydropower operations and then distributes among districts and regions of the country. Larger, wealthier districts, which receive larger amounts of general revenues from the central government, also receive larger allocations of hydropower revenues. The per capita shares of hydropower revenue are notably larger in the Central andWestern Regions, which are home to most of Nepal’s hydropower facilities. Thus, the revenue sharing program does not favor poorer districts and regions with little hydropower development. Further, the hydropower revenue allocations to all development regions are small portions of the general revenues they receive. Consequently, the program is unlikely to have a substantial impact on economic development in poorer districts and regions.